CROSS-CULTURAL ASPECTS OF PROJECT MANAGEMENT: SERBIA GOES TO IRAQ FOR JORDAN PROJECT - Jovanovic, Petar; Obradovic, Vladimir; Petrovic, Dejan; Mihic, Marko; Jovanovic, Aca (International Journal of Industrial Engineering: Theory, Applications and Practice, 2009)
The global expansion of the contemporary business have caused the internationalization of projects and project management as well. Parallel, project management is not considered a technique for planning and execution of projects any more, but becomes a sophisticated tool for achieving strategic goals and competitive advantage. Regarding these trends, it seems that standard and widely accepted project management methodologies do not provide enough for reaching project business excellence. This article proposes certain adjustments of these approaches in order to achieve better project results. The paper especially focuses on the cross cultural aspects of international projects and their impacts on the project performance.